Exploring the hole cleaning parameters of horizontal wellbore using two-phase Eulerian CFD approach. (March 2016) - Dewangan, Satish K; Sinha, Shobha L
The present investigation deals with the flow through concentric annulus with the inner cylinder in rotation. This work has got its importance in the petroleum industries in relation to the wellbore drilling. In wellbore drilling, the issue of the hole-cleaning is very serious problem especially in case of the horizontal drilling process. The effect of the various parameters like slurry flow velocity, inner cylinder rotational speed, inlet solid concentration which affect hole cleaning was discussed. Their effect on the pressure drop, wall shear stress, mixture turbulence kinetic energy, and solid-phase velocity and slip velocity were analyzed, which are responsible for solid-phase distribution. Flow was considered to be steady, incompressible and two-phase slurry flow with water as carrier fluid and silica sand as the secondary phase. Eulerian approach was used for modeling the slurry flow. Silica sand was considered of spherical shape with particle size of 180 µm. ANSYS FLUENT software was used for modeling and solution. Plotting was done using Tecplot software and Microsoft Office.